Implementasi Lesson Study dalam Pembelajaran Matematika Kelas VIII SMP N 1 Kotabaru Karawang Menggunakan Pendekatan Model Pembelajaran Contextual Teaching and Learning - Intan Shofiyanti (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study aims to improve students' mathematics learning outcomes through the implementation of Lesson Study with the Contextual Teaching and Learning (CTL) approach. Lesson Study was conducted in two cycles following the Plan-Do-See stages, involving teacher collaboration in planning, implementing, and reflecting on the learning process. The CTL approach was utilized to connect mathematics material to real-life contexts, making learning more meaningful and relevant. The results of the study indicate that the implementation of Lesson Study with the CTL approach significantly enhances students' understanding of the material, strengthens their engagement in learning, and provides a more effective learning experience. These findings suggest that the combination of Lesson Study and CTL can be an effective strategy in mathematics instruction to improve students' learning outcomes.